Twist-Related Speckle Variation in Graded-Index Multimode Fiber - Hongye Li; Yange Liu; Hu Liang; Simeng Han; Zhi Wang (IEEE Photonics Journal)
We theoretically investigate a twist-related speckle variation in a graded-index multimode fiber. The simulation results show that by increasing the offset splicing distance between a single-mode fiber and a multimode fiber, the speckle pattern tends to be more chaotic. Also, the fiber length is a crucial parameter that affects speckle distribution, and the speckle pattern varies periodically along the torsional-less multimode fiber. By exerting twist on a multimode fiber, the speckle pattern revolves. The rotational angle ascends linearly with a twist angle and this tendency is not affected by an offset distance and a fiber length. The theoretic results disclose a twist-related coupling in the graded-index multimode fiber, provide a novel twist sensing method and show potential application in a high-power laser and an imaging field.